Komposisi dan Struktur Zooplankton di Danau Singkarak - Jenie Wulandari; Afrizal S; Jabang Nurdin (Jurnal Biologi Universitas Andalas, 2014)
The research about compotition and structure community of zooplankton in lake Singkarak has been done from March 2013 until May 2013. This study used purposive method and zooplankton sampling was done by using vertical filtering from 10 stations. The results shown that there were 16 species zooplankton with Crustacea (8 species), Protozoa (3 species) and Rotifera (5 species). Average population density of zooplankton were 32.43 ind./l with varying type on each station. Diversity index were 0.79-1.52 and highest was found at station II and IX (H’=1.73) and lowest was found at station IV (H’=1.73). Equitability index was 0.32-0.91% higest was found at station X (E=0.91) and lowest was found at station IV (E=0.32). Similarity index was 31.25-76.92%. Based on the diversity index of zooplankton show that the community was relatively stable. Key words : Singkarak, Zooplankton, Structure, Composition, Community